Midterm survival analysis of a cemented dual-mobility cup combined with bone impaction grafting in 102 revision hip arthroplasties. Issue 2 (March 2018) - Spaans, Elsa A.; Koenraadt, Koen L.M.; Wagenmakers, Robert; van den Hout, Joost A.A.M.; te Stroet, Martijn A.J.; Bolder, Stefan B.T.
Introduction: Revision hip arthroplasty is associated with higher dislocation rates than primary hip arthroplasty. A dual-mobility cup (DMC) can reduce this risk. Another problem is destruction of the acetabulum, induced by aseptic loosening of the prosthesis. Bone impaction grafting (BIG) can be used to reconstruct these defects, but is usually performed with cemented all polyethylene cups. The purpose of this study is to evaluate midterm cup survival and dislocation rate for the combination of BIG and DMC. Methods: Between 2007 and 2013, 96 patients received 102 DMCs combined with BIG of the acetabulum during revision surgery. These data were first compared with a control group, consisting of 59 cases from the same hospital receiving a cemented all polyethylene cup combined with BIG. In addition, the control group was expanded with 41 cases operated on in 2007 in 'an orthopaedic centre of excellence', resulting in a 'combined control group' of 100 patients. Log-rank tests and chi-square tests were used to compare survival and dislocation rates, respectively. Results: Cumulative survival of the DMC was 95.8% (range 3 months-7 years). This was comparable to the survival in the control groups (96.5% and 94.7%). The dislocation rate of 2.9% (3/102) in the dual-mobility group was lower (p = 0.02) compared to the dislocation rate of 11.8% (7/59) in the control group, but not (p = 0.12) compared to 8% in the combined control group (8/100). Conclusions: This study shows that combining a DMC with BIG does not compromise outcome in terms of midterm survival of the cup.